PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK ( SAK-ETAP) PADA JINGGA BATIK BUKITTINGGI - Dahlia Dahlia; Zelly Denofriza; Melda Melda (Jurnal Akuntansi Syariah (JAkSya), 2023)
This study aims to determine the financial statements at Jingga Batik Bukittinggi, to find out the financial statements according to SAK ETAP and also the suitability of the preparation of financial statements at Jingga Batik Bukittinggi with generally accepted accounting standards, namely SAK ETAP. This research uses quantitative descriptive method. The focus of research is documents or records related to financial statements. Sources of data in this study using primary and secondary data sources obtained from Owner Jingga Batik Bukittinggi. Data collection techniques using interview and documentation techniques. The results of the study found that the recording system carried out by Jingga Batik Bukittinggi was still very simple, only recording income and expenses. Financial statements according to SAK ETAP consist of income statements, statements of changes in equity, statements of financial position, statements of cash flows, and notes to financial statements. Jingga Batik Bukittinggi has not prepared financial reports in accordance with generally accepted standards due to limited knowledge and understanding in the field of accounting so that the preparation of financial statements is not in accordance with SAK ETAP.